2012
DOI: 10.1007/s10067-012-1983-7
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the Persian versions of WOMAC Osteoarthritis Index and Lequesne Algofunctional Index

Abstract: The WOMAC Osteoarthritis Index and Lequesne Algofunctional Index have not been translated and validated for Iranian patients with osteoarthritis (OA) of the knee or hip. The aim of this study was to validate the Persian form of WOMAC OA Index and Lequesne Algofunctional Index and to assess their test-retest reliability and convergent validity. Forward/backward translations and consensus panels were conducted to obtain the Persian versions of WOMAC OA Index and Lequesne Algofunctional Index. A non-probability s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 27 publications
5
46
1
Order By: Relevance
“…Similar studies demonstrated serious disability in their study populations with total Lequesne scores that ranged from 10.51 to 13.67 (11,14,17,18). In our study, the worst score for the Lequesne index was in the ADL domain; this was also reported in the study by Konstantinidis et al (11).…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Similar studies demonstrated serious disability in their study populations with total Lequesne scores that ranged from 10.51 to 13.67 (11,14,17,18). In our study, the worst score for the Lequesne index was in the ADL domain; this was also reported in the study by Konstantinidis et al (11).…”
Section: Resultssupporting
confidence: 89%
“…(11), a significant positive correlation only existed between age and the Lequesne distance subscale, indicating that the correlations of age with the other subscales were not significant. Education showed significant negative correlations with all of the Lequesne subscales in our study and in the study by Nadrian et al (17). Moreover, we found significant positive correlations between the duration of disease and all of the Lequesne subscales before and after rehabilitation, while Nadrian et al (17) observed a significant positive correlation between the pain domain and the total Lequesne score and also between the Lequesne distance and ADL subscale scores.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations